Orthoptera (Caelifera) and its entomopathogens fungi in maize agroecosystems in Erongarícuaro, Michoacán - Quesada Béjar, Venecia; Nájera R., Miguel B.; Reyes-Novelo, Enrique; González-Esquivel., Carlos E. (Revista Mexicana de Ciencias Agrícolas, 2017)
Grasshoppers are a major pest of maize, one of its natural enemies are entomopathogenic fungi (HEP). Proper management of this crop, involving changes in the microhabitat, can contribute to the control of grasshopper populations, as well as the presence of its natural enemies. The effect of two types of agricultural management was evaluated: monoculture (MC-I) of maize and polyculture of maize, pumpkin and bean (PC-I), as well as the vegetation of the monoculture margins (VMM) and the vegetation of the polyculture margins (VMP) on the richness and abundance of grasshoppers and its associated entomopathogenic fungi (HEP) in Erongarícuaro, Michoacán. Grasshoppers were collected monthly with a striking net from July to December 2015 on two plots of each management type and its marginal vegetation at three sites. The grasshopper community (CS) consisted of 17 species, where Sphenarium purpurascens purpurascens Charpentier, was the dominant species (97.8% abundance). The type of agricultural management had no effect on species richness. Richness in the marginal vegetation of the crops did not explain the richness in MC-I and PC-I; however, abundance of S. p. purpurascens in marginal vegetation explained the abundance found in the MC-I and PC-I sites. From the 2920 grasshoppers collected in, 0.41% were infected by Metarhizium Sorokin or Beauveria (Balsamo) Vuillemin. The most frequently infected HEP was Metarhizium. The proportion of infected individuals and PC-I conditions were positively related, compared to VMP. The sites with greater vegetal diversity had greater abundance of grasshoppers and greater infection with HEP.
Keywords: Sphenarium purpurascens purpurascens, Metarhizium, Beauveria, Grasshopper